INMATES’ COPING STRESS STRATEGIES AT CLASS IIA CORRECTIONAL INSTITUTION OF KOTABUMI - M Akbar Rizky; Mulyani Rahayu (Universitas Nusa Cendana, 2026)
This study examines the issue of low self-efficacy and self-confidence among Children in Conflict with the Law during their rehabilitation at Pusat Pelayanan Sosial Griya Bina Karsa. The research aims to identify the role of self-efficacy in improving children’s confidence and abilities throughout the rehabilitation process. Using a qualitative case study approach, data were collected through in-depth interviews and observations involving child clients, community counselors, and social workers. The findings reveal that interventions such as skills training, non-formal education, and social support play a significant role in enhancing children’s self-efficacy. These efforts help improve their confidence, adaptability, and readiness to reintegrate into society while reducing the risk of reoffending. The development of self-efficacy occurs gradually through strengthening motivational, cognitive, and emotional aspects. These findings highlight that self-efficacy is a crucial foundation for building positive behavior and supporting successful social reintegration among children undergoing rehabilitation. Keywords: Coping Strategy; Stress; Prison; Emotion-Focused; Problem-Focused